Effects of -NO2 and -NH2 functional groups in mixed-linker Zr-based MOFs on gas adsorption of CO2 and CH4 - Rada, Z.; Abid, H.; Sun, Hongqi; Shang, J.; Li, J.; He, Y.; Liu, Shaomin; Wang, Shaobin (Elsevier Ltd, 2018)
This study was undertaken to evaluate the effects of mixing BDC-NO 2 and BDC-NH 2 linkers in the synthesis of Zr-based metal organic frameworks (Zr-MOFs) on their adsorption and separation of CO 2 and CH 4 . UiO-66 with single or binary -NO 2 and -NH 2 samples were synthesized under solvothermal conditions and activated by solvent exchanging using methanol. Structural analyses of the materials were conducted using FTIR, XRD, TGA, SEM, 1 HNMR and N 2 adsorption/desorption techniques and adsorption of CO 2 and CH 4 at high pressures and different temperatures (273 and 298 K) was investigated. It was found that UiO-66-NH 2 exhibited higher CO 2 and CH 4 adsorption capacities than those of UiO-66-NO 2 . Addition of -NH 2 functional group in UiO-66-NO 2 could enhance CO 2 and CH 4 adsorption due to the extra CO 2 adsorption sites of -NH 2 functional groups. Addition of -NO 2 functional group to UiO-66-NH 2 at a low loading could also increase CO 2 and CH 4 adsorption, however, a high loading of NO 2 functional group to UiO-66-NH 2 would result in decreased adsorption.